Hematology Profiles and Performance of Broiler Chickens Fed on Commercial Feed - Sufiriyanto, Sufiriyanto; Iriyanti, Ning; Susanti, Emmy (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
The objective of this research was to investigate the effect of commercial feed on hematological and carcass profiles of broiler chickens. A total of 1800 day old chick (DOC) broilers were administered in a Completely Randomized Design (CRD) furthered by Duncan test. The treatments consisted of Feed A, B, C, D, E, and F.Â The observed variables included hematology profiles (erythrocyte, hemoglobin, leukocyte, heterophil, lymphocyte, and monocyte) and performance (live weight, carcass percentage, breast, thigh, wings, shank, and head).Â The result showed that feed treatment did not significantly affect (P>0,05) hematology profiles and performance of broiler chickens, but significantly affected live weight (P<0,05). Conclusively, different types of commercial feed did not render physiological effect to DOC and safe for feeding until 35 days old to increase the live weight ofÂ broiler chickens.